Expression of HOXC10 gene regulates the growth and invasion of prostate cancer cells (Bangladesh Journal of Pharmacology, 2021)
The present study was undertaken to decipher the role of HOXC10 gene in regulating the growth and metastasis of prostate cancer. The results revealed significant (p